THE IMPACTS OF CORPORATE GOVERNANCE MECHANISMS AND OWNERSHIP STRUCTURE ON CAPITAL STRUCTURE OF CHINESE DUAL-LISTED COMPANIES - Wing Kwong, Chan; Ei Yet, Chu (International Journal of Business and Society, 2023)
This research aims to assess how the mechanisms of corporate governance and ownership structure affect the capital structures of Chinese dual-listed companies that list their shares in the China A-share market and the Hong Kong market simultaneously from 2003 to 2019. A binary variable of state control firm attribute is introduced to proxy the political connection to the Chinese government. Both the independent director ratio and CEO duality are negatively and significantly associated with the long-term debt ratio. The board size negatively and significantly relates to the short-term debt ratio. Evidence of board members’ avoidance of investors’ pressure to use more debt and escape from debt lenders’ monitoring is observed in this research. Both foreign ownership and state ownership are significantly and negatively associate with the short-term debt ratio, but significantly and positively associate with the long-term debt ratio. Thus, both foreign investors and the Chinese government prefer the companies to achieve rapid growth through the use of more long-term debts. The binary variable of state control firm attribute has a significant positive association with the short-term debt ratio alone. However, evidence of declining use of long-term debt financing due to political connections, such as the issuance of equity, is not observed.